Is an "Affiliate Marketer a Decent Work for Generation Z in Indonesia?" - Nugraha, Arlan; Aulia Pratiwi, Monica; Muharni Ardenis, Dwi; Amany, Nurfatimah; Ahmad, Sarah Sabir; Sukmawati, Anggraini (TIJAB (The International Journal of Applied Business), 2024)
Background: Affiliate marketers have grown significantly as they serve as promoters, connecting e-commerce platforms with social media audiences and providing profitable income opportunities. Objective: This study assesses the alignment between affiliate marketing practices in Indonesia and the decent work indicator as defined by the International Labor Organization (ILO). Additionally, the study aims to compare respondents' income before and after engaging in affiliate marketing. Method: This study employed random sampling to select a sample of 25 affiliate marketers from the Jabodetabek region in Indonesia. Participants responded to 23 questions developed based on the 11 Decent Work Indicators established by the ILO, utilizing a 1 to 4 ordinal scale. The research utilized k-nearest neighbors clustering analysis to categorize respondents into groups aligning with the ILO's decent work indicators. To assess changes in respondents' income, paired Wilcoxon tests were employed. Results: Exploratory data analysis indicates that Indicators 1 (Employment opportunities) and 7 (Equal opportunity and treatment in employment) align well with ILO's indicators. Cluster analysis confirms that Indicators 1 and 7 share a high-performance group. In contrast, Indicators 6 (Stability and security of work) and 9 (Social security) exhibit the lowest alignment. There is no statistically significant income difference before and after becoming affiliate marketers. Conclusion: Exploratory data analysis indicates that Indicators 1 (Employment opportunities) and 7 (Equal opportunity and treatment in employment) align well with ILO's indicators. Cluster analysis confirms that Indicators 1 and 7 share a high-performance group. In contrast, Indicators 6 (Stability and security of work) and 9 (Social security) exhibit the lowest alignment. There is no statistically significant income difference before and after becoming affiliate marketers. Keywords: Affiliate marketing, Decent work indicators, International Labor Organization, Social security